2015
DOI: 10.5198/jtlu.2015.416
|View full text |Cite
|
Sign up to set email alerts
|

Method to adjust Institute of Transportation Engineers vehicle trip-generation estimates in smart-growth areas

Abstract: This paper describes a practical method of adjusting existing Institute of Transportation Engineers (ITE) estimates to produce more accurate estimates of motor-vehicle trip-generation at developments in smartgrowth areas. Two linear regression equations, one for an A.M. peak-hour adjustment and one for a P.M. peak-hour adjustment, were developed using vehicle trip counts and easily measured site and surrounding area context variables from a sample of 50 smart-growth sites in California. Many of the contextual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 13 publications
0
42
0
Order By: Relevance
“…Generation Handbook (Institute of Transportation Engineers, 2014), but in recent years, a 45 growing number of data and methods have been made available through studies in academia and 46 practice, e.g., Ewing et al, 2011;Schneider et al, 2015). These data are 47 used for a variety of purposes including, but not limited to: transportation impact analysis, 48 transportation system development charges, impact or utility fees, re-zoning, scaling or scoping 49 projects, and estimating greenhouse gas emission impacts of personal driving vehicles.…”
Section: Model Form For Trip Generation Models 39mentioning
confidence: 99%
See 2 more Smart Citations
“…Generation Handbook (Institute of Transportation Engineers, 2014), but in recent years, a 45 growing number of data and methods have been made available through studies in academia and 46 practice, e.g., Ewing et al, 2011;Schneider et al, 2015). These data are 47 used for a variety of purposes including, but not limited to: transportation impact analysis, 48 transportation system development charges, impact or utility fees, re-zoning, scaling or scoping 49 projects, and estimating greenhouse gas emission impacts of personal driving vehicles.…”
Section: Model Form For Trip Generation Models 39mentioning
confidence: 99%
“…In the second case study, the semi-log PM peak model from the California SGTG study 279 (Schneider et al, 2015) is evaluated using the data published online . 280…”
Section: California Smart Growth Trip Generation (Sgtg) Study Semi-lomentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there have been numerous efforts devoted to the collection of multimodal trip generation data, development of models that account for the built environment, and revisions to ITE's Trip Generation Handbook (2014) 1 to incorporate new recommendations for practice. Many studies have identified important features of the surrounding built environment that most impact trip rates and mode shares (Clifton, Currans, & Muhs, 2015;Schneider, Shafizadeh, & Handy, 2015), building on a long line of research on transportation and the built environment (Cevero & Kockelman, 1997;Ewing & Cevero, 2010;Handy S., 1992).…”
Section: Introductionmentioning
confidence: 99%
“…While the travel patterns and needs of low-income households have been documented in research, this information has yet to be incorporated into methods for reviewing the impacts of new housing development (Clifton et al, 2013;Schneider, Shafizadeh, Sperry, & Handy, 2013;Dock et al, 2015) and builds off of research focusing on housing and commercial land uses previously completed in California (Kimley-Horn and Associates, Inc., Economic & Planning Systems, & Gene Bregman & Associates, 2009;Schneider et al 2015). The industry standards for estimating transportation impacts are the data and methods presented in the Institute of Transportation Engineers' (ITE) Trip Generation Handbook (2014); but as yet, there are no standard methods or available data to differentiate the transportation impacts of affordable housing developments (as compared to market-rate housing) across urban, suburban, or rural contexts in the U.S.…”
Section: Introductionmentioning
confidence: 99%